Best Answer

simplify both sides of the equation:

1/3h+(-4)(2/3h)+(-4)(-3)=2/3h+-6 ~ distribute that

1/3h+-8/3h+12=2/3h+-6

(*1/3h+-8/3h*)+(**12**)=2/3h-6 ~ combine like terms for this

*-7/3h*+**12**=2/3h-6

-7/3h+12=2/3h-6

subtract 2/3h from both sides:

-7/3h+12-_2/3h=_2/3h-6-*2/3h*

-3h+12=6

subtract 12 from both sides:

-3h+12-*12=*-6-*12*

-3h=-18

divide both sides by -3

-3h/*-3*=-18/*-3*

h=6

Study guides

☆☆

Q: 1/3h - 4 (2/3h - 3) = 2/3h - 6?

Write your answer...

Submit

Still have questions?

Related questions

hi Im vienna it take about 6 13h

4 - 3 - 3 + 4 + 4 = 6

The mean for 3,6,3,2,and 4 is 4. 3 + 6 + 3 + 2 + 4 + 6 = 24 24 / 6 = 4

smells like teen spirit by nirvana the tab for the intro is e|-----------------|------------------|-----------------|------------------| B|-----------------|------------------|-----------------|------------------| G|-------------3-3-|-0------------6-6-|-------------3-3-|-0------------6-6-| D|-3--3-3-xxxx-3-3-|-06--6-6-xxxx-6-6-|-3--3-3-xxxx-3-3-|-06--6-6-xxxx-6-6-| A|-3--3-3-xxxx-1-1-|-06--6-6-xxxx-4-4-|-3--3-3-xxxx-1-1-|-06--6-6-xxxx-4-4-| E|-1--1-1-xxxx-----|--4--4-4-xxxx-----|-1--1-1-xxxx-----|--4--4-4-xxxx-----| Guitar (heavy dist) e|-----------------|------------------|-----------------|------------------| B|-----------------|------------------|-----------------|------------------| G|-------------3-3-|-0------------6-6-|-------------3-3-|-0------------6-6-| D|-3--3-3-xxxx-3-3-|-06--6-6-xxxx-6-6-|-3--3-3-xxxx-3-3-|-06--6-6-xxxx-6-6-| A|-3--3-3-xxxx-1-1-|-06--6-6-xxxx-4-4-|-3--3-3-xxxx-1-1-|-06--6-6-xxxx-4-4-| E|-1--1-1-xxxx-----|--4--4-4-xxxx-----|-1--1-1-xxxx-----|--4--4-4-xxxx-----| e|-----------------|------------------|-----------------|------------------| B|-----------------|------------------|-----------------|------------------| G|-------------3-3-|-0------------6-6-|-------------3-3-|-0------------6-6-| D|-3--3-3-xxxx-3-3-|-06--6-6-xxxx-6-6-|-3--3-3-xxxx-3-3-|-06--6-6-xxxx-6-6-| A|-3--3-3-xxxx-1-1-|-06--6-6-xxxx-4-4-|-3--3-3-xxxx-1-1-|-06--6-6-xxxx-4-4-| E|-1--1-1-xxxx-----|--4--4-4-xxxx-----|-1--1-1-xxxx-----|--4--4-4-xxxx-----|

6 1/2 - 3 3/4. Convert 1/2 to fourths =(2/4) --> 6 2/4 - 3 3/4. You can borrow one (4/4) from the 6, so 6 2/4 = 5 6/4, then you can subtract:5 6/4 - 3 3/4 = 2 3/4

12 is the LCM of any of the following 44 sets:{12},{1, 12}, {2, 12}, {3, 4}, {3, 12}, {4, 6} , {4, 12}, {6, 12},{1, 2, 12}, {1, 3, 4}, {1, 3, 12}, {1, 4, 6}, {1, 4, 12},{1, 6, 12}, {2, 3, 4}, {2, 3, 12}, {2, 4, 6}, {2, 4, 12},{2, 6, 12}, {3, 4, 6}, {3, 4, 12}, {3, 6, 12}, {4, 6, 12},{1, 2, 3, 12}, {1, 2, 4, 12}, {1, 2, 6, 12}, {1, 3, 4, 12},{1, 3, 6, 12}, {1, 4, 6, 12}, {1, 2, 4, 6}, {1, 3, 4, 6},{1, 2, 3, 4}, {2, 3, 4, 6}, {2, 3, 4, 12}, {2, 3, 6, 12},{2, 4, 6, 12}, {3, 4, 6, 12},{1, 2, 3, 4, 6}, {1, 2, 3, 4, 12}, {1, 2, 3, 6, 12},{1, 2, 4, 6, 12}, {1, 3, 4, 6, 12}, {2, 3, 4, 6, 12},{1, 2, 3, 4, 6, 12}.

2/3 + 4/6 =4/6 + 4/6 =8/6 =4/3 or =1 1/3

4. 3+3+6=12÷3=4

2/3+ 4/6 4/6+4/6= 8/6=4/3 1 and 1/3

lcm(3, 4) = 12 lcm(3, 6) = 6 lcm(4, 6) = 12 lcm(3, 4, 6) = 12.

z = 3. If you mean (4*z + 6 )/3 then it is 6. (4*3 + 6) /3 = (12 + 6) /3 = 18/3 = 6 If you meant 4*z + (6/3) then it is 14. 4*3 + (6/3) = 12 + 2 = 14.

Answer = 6 / (3/4) = 6 x 4 / 3 = 8 quart cans each of 3/4 quartThe idea is to divide 6 by 3/4, which is the same as 6 times 4/3.

People also asked